A qualitative study of leadership styles of successful women entrepreneurs in Malaysia - Cheng, Wei Hin; Md Isa, Filzah; Sangaralingam, Jayaeswari (2012)
This paper examined the leadership styles and motivational factors of successful women entrepreneurs.Women entrepreneurs play an important role in the development of a country’s economy.Women today made up more than 47 percent of the labor force in Malaysia.Past research on entrepreneurs demonstrated that individuals with entrepreneurial leadership distinguished them from non entrepreneurs. This research was done to explore entrepreneurial leadership styles and personality characteristics of the entrepreneurs The research is a qualitative research which involved interviews with successful women entrepreneurs.